ABOUT PEDAGOGICAL TECHNOLOGIES IN VOCATIONAL SPEECH TRAINING - Ludmila G. Noskova (Высшее образование в России)
The article addresses issues of vocational speech training, acquisition and mastering of students' written and oral speech. The author dwells on methodic aspects of formation of such skills as reading/hearing and understanding of texts, and also on formation of the ability to produce texts of various types and genres. Speech preparation includes personally social, personally professional interdependent components and forms, involves development of other personal and professional qualities, and stimulates professionalism growth. Analyzing various forms of the organization of educational process when studying rhetoric, the author suggests to get acquainted with an experience relying on the pedagogical principles of changing training stereotypes. This process requires succession, staging, and a definite set of professional speech genres taking into account all disciplines within curriculum. This approach allows to integrate speech-related disciplines with all other disciplines, and thus to intensify continuous process of education.